2018
DOI: 10.1049/iet-epa.2018.0150
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic design optimisation of an interior permanent‐magnet synchronous motor by the multi‐objective approach

Abstract: In engineering terms, it is always desirable to maximise the efficiency of the motor and to look the problem in economic viewpoint, minimisation of the weight and cost of the motor is required. As these two aspects are like two sides of a coin, it is usually aimed to acquire the best efficiency per weight and cost. As a result, the performance improvement of permanent-magnet synchronous motor (PMSM) has two sides: technical and economic. This study proposes a new approach for design optimisation of an interior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The optimal design for a PMSM can be created by combining design methods such as analytical models [1,2], magnetic equivalent circuit (MEC) models [3,4], and finite element analysis (FEA) [5][6][7][8] with an optimal design algorithm. Although these design methods have their advantages, the FEA optimization method combined with the optimal design algorithm has the highest accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal design for a PMSM can be created by combining design methods such as analytical models [1,2], magnetic equivalent circuit (MEC) models [3,4], and finite element analysis (FEA) [5][6][7][8] with an optimal design algorithm. Although these design methods have their advantages, the FEA optimization method combined with the optimal design algorithm has the highest accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is a lot of research on multi-objective design optimisation of motor. In general, there are three methods for multi-objective design optimisation of motor: linear analytical model [6][7][8][9], magnetic equivalent circuits (MEC) model [10][11][12][13][14], and finite element analysis (FEA) model [15][16][17][18][19][20][21], all of them can be combined with modern optimisation algorithms such as non-dominated sorting GA-II, artificial bee colony algorithm, modified particle swarm optimisation (MPSO) etc [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal design is a method of finding the values of design variables to obtain an optimal solution within a range of constraints. The optimal design for PMSMs is created by combining design methods such as the analytical model, magnetic equivalent circuits (MEC) model, and finite element analysis (FEA) with optimal design algorithms [1][2][3][4][5][6][7][8]. First of all, there are studies on optimal design using the analytical model [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The stator current was optimized considering magnetic saturation using an analytical expression. The following are studies on optimization using the MEC model [3,4]. In [3] it was reported that the MEC optimization method combined with an optimization algorithm can optimize the volume and energy loss of a PMSM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation